Cancer-associated glycoforms of gelatinase B exhibit a decreased level of binding to galectin-3. - Fry, SA; Van den Steen, P; Royle, L; Wormald, M; Leathem, A; Opdenakker, G; McDonnell, J; Dwek, R; Rudd, P (2006)
Gelatinase B (MMP-9) and galectin-3 are widely known to participate in tumor cell invasion and metastasis. Glycans derived from MMP-9 expressed in MCF-7 breast cancer and THP-1 myeloid leukemia cells were compared with those from MMP-9 expressed in natural neutrophils. The many O-linked glycans of neutrophil gelatinase B presented a cluster of mainly galactosylated core II structures, 46% of which were ligands for galectin-3; 11% contained two to three N-acetyllactosamine repeating units that are high-affinity ligands for the lectin. The glycan epitopes thus provide MMP-9 with both high-affinity and (presumably) high-avidity interactions with galectin-3. In contrast, the O-glycans released from MMP-9 expressed in MCF-7 and THP-1 cells were predominantly sialylated core I structures. Only 10% of MCF-7 and THP-1 gelatinase B O-glycans were ligands for galectin-3 and contained only a maximum single N-acetyllactosamine repeat. Consistent with the glycan analysis, surface plasmon resonance binding assays indicated that the cancer-associated glycoforms of MMP-9 bound galectin-3 with an affinity and avidity significantly reduced compared with those of the natural neutrophil MMP-9. Galectin-3 exists as a multimer that also binds laminin, providing a means of localizing neutrophil MMP-9 in the extracellular matrix (ECM). The analytical data presented here suggest that MMP-9 glycoforms secreted by tumor cells are unlikely to be tethered at the site of secretion, thus promoting more extensive cleavage of the ECM and providing a rationale for the contribution that gelatinase B makes to cancer cell metastasis.